Detection and Counting of Blood Cells in Blood Smear Image - Pradeep, K.; Ganthimathi, C.; Harini, K.; Diddha, N. (Asian Journal of Engineering and Applied Technology, 2016)
This paper deals with an image processing technique used for detecting the blood cells in less time. The proposed technique also helps in counting and segregating the blood cells in blood smear image of different categories based on the form factor using various Morphological operations. Nowadays in Hospitals and clinical Laboratories the waiting time for getting their blood results and reports are more commonly 24 hours to 8 days in case of high severity diseases where the mortality rates are high. Doctors and technicians in healthcare sectors recommended that the patient’s waiting time should be as less as possible and the treatment should be started immediately for the high risk diseases like Hepatitis B. The major other factor affects patient in healthcare field is the more expensive pathological tests which sometimes leading to loss of patient’s life. The proposed technique gives improved accuracy in counting the number of blood cells in blood smear image in compare to manual counting in laboratories.